Some Reflections on the Institutions of Muslim Spain - Roberto Marín-Guzmán (American Journal of Islam and Society, 2004)
This essay analyzes the major political, military, and administrative institutions of al-Andalus (Muslim Spain) and explains how they gave a sense of unity to the Abode of Islam (dar al-Islam) by replicating the same institutions used in the East (al- Mashriq). The military institutions (e.g., jund, thughur, and husun) helped to keep Muslim Spain safe from enemy attacks, both Christian and Muslim, and to suppress all revolts, while the political institutions enabled the authorities to keep al-Andalus unified, levy taxes, administer the cities (sahib al-madinah), supervise the markets (sahib al-suq), and, finally, to administer the region’s provinces (kuwar).